A Legal Analysis of Regulatory Gaps in Addressing Cyber Harassment and Online Gender-Based Violence in Sri Lanka - Ranawaka, R.A.Y.A.W. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
While several laws addressing cyber harassment and online gender-based violence (OGBV) exist at national and international levels in Sri Lanka, the legal framework remains insufficient to respond effectively to the rapidly evolving nature of technology-facilitated abuse. This paper examines, through doctrinal legal analysis, the adequacy of current legislative measures in Sri Lanka for providing protection against cyber harassment and OGBV and identifies substantive and procedural gaps that limit access to justice and victim protection. The study further compares Sri Lanka’s legal framework with those of India, the United Kingdom, and Australia to assess best practices and emerging standards. This comparison highlights major deficiencies in Sri Lanka’s approach, including the absence of a comprehensive definition of OGBV, limited recognition of technology-facilitated coercive control, and inadequate measures for preserving and presenting digital evidence. Additionally, the lack of specialized reporting mechanisms and investigative structures for cyber-violence weakens the effectiveness of existing laws. The research also identifies systemic challenges faced by victims in accessing justice, such as limited digital literacy among law enforcement, delays in obtaining information from digital platforms, and the absence of specialized cyber-violence units with gender-sensitive training. In conclusion, the paper argues that Sri Lanka’s legal responses require urgent reform to address technology-enabled violence. It proposes adopting a comprehensive legislative framework with clear definitions, enhanced investigative powers, streamlined evidentiary procedures, and inter-agency coordination. Finally, it recommends aligning national laws with international standards, including the International Covenant on Civil and Political Rights (ICCPR), the Council of Europe’s Istanbul Convention, and emerging global best practices, to ensure effective victim protection and deter cyber-enabled gender-based violence.
Keywords: Online gender-based violence (OGBV); Cyber harassment; Digital abuse; Cybercrime law; Computer crimes act